2006
DOI: 10.1128/mcb.01868-05
|View full text |Cite
|
Sign up to set email alerts
|

Insulin-Like Growth Factor I Controls a Mutually Exclusive Association of RACK1 with Protein Phosphatase 2A and β1 Integrin To Promote Cell Migration

Abstract: The WD repeat scaffolding protein RACK1 can mediate integration of the insulin-like growth factor I receptor (IGF-IR) and integrin signaling in transformed cells. To address the mechanism of RACK1 function, we searched for regulatory proteins that associate with RACK1 in an IGF-I-dependent manner. The serine threonine phosphatase protein phosphatase 2A (PP2A) was found associated with RACK1 in serum-starved cells, and it dissociated immediately upon stimulation with IGF-I. This dissociation of PP2A from RACK1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
107
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 97 publications
(114 citation statements)
references
References 42 publications
7
107
0
Order By: Relevance
“…Here we showed that RACK1 recruited both PP2A and Akt in response to ephrin-B1-Fc-induced activation of EphB3, facilitating the phosphatase/substrate interaction by serving as a scaffold, and consequently abrogated Akt activity. Previous observations have shown that PP2A can interact with RACK1 in some circumstances [39][40][41] . For example, insulin-like growth factor 1 (IGF-1) controls the mutually exclusive association of RACK1 with PP2A and β1 integrin.…”
Section: Discussionmentioning
confidence: 99%
“…Here we showed that RACK1 recruited both PP2A and Akt in response to ephrin-B1-Fc-induced activation of EphB3, facilitating the phosphatase/substrate interaction by serving as a scaffold, and consequently abrogated Akt activity. Previous observations have shown that PP2A can interact with RACK1 in some circumstances [39][40][41] . For example, insulin-like growth factor 1 (IGF-1) controls the mutually exclusive association of RACK1 with PP2A and β1 integrin.…”
Section: Discussionmentioning
confidence: 99%
“…S1), were used for vector-based small hairpin RNA expression. The two sequences are: siRACK1-a (20 nt, GAC CAT CAT CAT GTG GAA GC), which was designed to target rat and human RACK1 mRNA using the online siRNA Retriever (available from Cold Spring Harbor Laboratories), and siRACK1-b (19 nt, CCA TCA AGC TAT GGA ATA C), which targets the human gene (12). For cloning of each of the siRACK1s, two complementary oligonucleotides were synthesized as follows: 5Ј-GATCCC (20 nt, sense) TTGAT-ATCCG (20 nt, antisense) TTTTTT CCAAA-3Ј and 3Ј-GG (20 nt antisense) AACTATAGGC (20 nt, sense) AAAAAA GGTTTTCGA-5Ј flanked by BamHI and HindIII residues.…”
Section: Methodsmentioning
confidence: 99%
“…These interactions, and others, put RACK1 at a focal point for spatial and temporal regulation of various signaling cascades. For example, in transformed cultured cancer cells, RACK1 was shown to form a scaffolding complex that includes the IGF-1R, ␤1 integrin, and focal adhesion kinase (6,9,10,12). In addition, RACK1 is also found at the 40 S ribosomal subunit (3,13,14) and was shown to bridge protein kinase C-mediated signaling to the ribosomal translation machinery (15).…”
mentioning
confidence: 99%
“…We have previously established that PP2A competes with β1 integrin for binding to WD7 of RACK1 and that the binding was regulated by IGF-I and required for IGF-I-mediated cell adhesion [30,31]. We set out to further characterise the interaction between RACK1 and the PP2A holoenzyme.…”
Section: Mapping the Interaction Between Rack1 And The Pp2a-c Subunitmentioning
confidence: 99%
“…PP2A directly interacts with RACK1 in an IGF-1 dependent manner where RACK1 serves to stabilise PP2A activity [30,31]. A reduction in RACK1 expression decreases the phosphatase activity of PP2A, which has been shown to promote cell migration in cancer cells [31].…”
Section: Introductionmentioning
confidence: 99%